Kidney Check Point-of-Care Testing—Furthering Patient Engagement and Patient-Centered Care in Canada's Rural and Remote Indigenous Communities: Program Report. (March 2021) - Curtis, Sarah; Martin, Heather; DiNella, Michelle; Lavallee, Barry; Chartrand, Caroline; McLeod, Lorraine; Woods, Cathy; Dart, Allison; Tangri, Navdeep; Rigatto, Claudio; Komenda, Paul
Purpose of program: Access to health care services remains a significant barrier for many Indigenous people's living in rural and remote regions of Canada. Driven by geographical isolation and compounded by socioeconomic and environmental disparities, individuals living under these circumstances face disproportionately poor health outcomes. Kidney Check is a comprehensive screening, triage, and treatment initiative working to bring culturally safe preventive care to rural and remote Indigenous communities across Manitoba, Ontario, BC, Alberta, and Saskatchewan. The project's patient-oriented approach addresses concerns raised by kidney patients and their caregivers using culturally safe practices. Using the various expertise of their multidisciplinary team, Kidney Check seeks to further collaborative efforts to improve access to preventive health care for these groups. Meaningful engagement with patients, communities, and local health care stakeholders ensures Indigenous voices are heard and incorporated into the project in a way that promotes shared decision-making and sustainability. Sources of information: As an affiliate program of the Can-SOLVE CKD Network, Kidney Check's guiding priorities were developed over 3 years of patient consultation and finalized during 2 workshops held with more than 30 patients, caregivers, Indigenous peoples, researchers, and policy makers using a modified Delphi process. Today, patients continue to participate in project development via 2 governing bodies: The Patient Governance Circle and the Indigenous Peoples Engagement and Research Council (IPERC). Methods: Modeled after the Indigenous-led 2015 FINISHED project in Manitoba, Kidney Check employs point-of-care testing to identify diabetes, hypertension, and chronic kidney disease (CKD) in individuals, ages 10 and above, regardless of pre-existing risk factors. The Kidney Check team consists of 4 working groups: project leadership, provincial management, local community partners, and patient partners. By using and building on existing relationships between local and provincial health care stakeholders and various Indigenous communities, the program furthers collaborative efforts to bridge gaps in health equity. Key findings: The Kidney Check program has established an infrastructure that integrates patient engagement at all stages of the program from priority setting to deployment and dissemination strategies. Limitations: While we encourage and offer screening services to all, many still choose not to attend for a variety of reasons which may introduce selection bias. Kidney Check uses patient engagement as a foundational component of the program; however, there is currently a limited amount of research documenting the benefits of patient engagement in health care settings. More formal qualitative evaluations of these activities are needed. In addition, as the COVID-19 pandemic has halted screening procedures in most communities, we currently do not have quantitative data to support the efficacy of the Kidney Check program. Implications: For many Indigenous people, lack of accessibility to health care services is compounded by sociopolitical barriers that disrupt relationships between patients and providers. Meaningful engagement presents one opportunity to ensure the voices and perspectives of Indigenous patients and communities are incorporated into health services. In addition, this screening paradigm has shown to be cost effective as shown by analyses done on the FINISHED screening program.